# Establish the equation of motion of a damped oscillator and show that for a weakly damped oscillator, the displacement is given by ( ) exp( )cos( ) x t = a0 −bt ωd t + φ where symbols have their usual meanings.

1
by aarzu

2015-04-13T20:59:23+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let us take a spring mass system with a natural frequency ω0.
m = mass of the body oscillating
Spring restoration force F = - k x ,      k = spring constant.
Damping force  F_d = - b v  ,    where  b = damping factor.

x = displacement.
v = velocity of mass.
ω₀ is the frequency of the spring mass when there is no damping.  Only force is spring force.
so,      m d² x / d t²  = - k x    has the solution:
x = A0 Sin (ω₀ + Ф₀)             --- (0)
and  ω₀ = √(k/m)       or  ω0² = k/m     ---- (12)
===========================
net force acting on mass m is:   F = - k x - b v      --- (1)
The minus sign is because spring restoration force is opposite to displacement direction and the damping force is in the direction opposite to velocity.

m a = m d² x / d t²  = - k x - b v
d² x /d t²  = -k/m * x - b/m * dx/dt            --- (2)

This is the equation of motion in the form of differential equation. The general solution for the above differential equation is in the following form:

let     x = A_t e^{-at}  Sin (ω' t + Ф')      --- (3)
we need to determine A_t, a, and ω'.

differentiate two times:
dx/dt = - a A_t e^{-at} Sin (ω't+Ф')+ + A_tω' e^{-a x}  Cos (ω't+Ф')     -- (4)
= A_t e^{-at} [ - a Sin ω't + ω' Cos ω't ]

d² x/d t² =  a² A_t e^{-at} Sin (ω't+Ф') - a A0 ω' e^{-at} Cos (ω't+Ф')
- A_t a ω' e^{-at} Cos (ω't+Ф') - A_t ω'² e^{-at} Sin (ω't+Ф')
= (a² - ω'²) A_t e^{-at} Sin (ω't+Ф')  -  2 A_t a ω'e^{-at} Cos (ω't+Ф')  --(5)

Find the RHS of equation (2)
-kx/m - b/m * dx/dt
= -k/m A_t e^{-at} Sin(ω't+Ф') - b/m A_t e^{-at} [- a Sin(ω't+Ф') + ω' Cos(ω't+Ф')]
= A_t e^{-at} Sin(ω't+Ф') [ -k/m + ab/m] - bω'/m A_t e^{-at} Cos(ω't+Ф') --(6)

Compare equations (5) and (6), we get :
(ab - k) / m = (a² - ω'²)    -- (7)
a = b/(2m)     =>     b = 2 a m         -- (8)

=>  2 a² - k / m = a² - ω'²
=>  ω'² = ( k/m  - a²)  = (ω₀² - a²) =  [ω₀² - b²/4m² ]
=>   ω' = √[ω₀² - b²/4m² ]           --- (9)
also the phase angle of the damped oscillation is :
Cos Ф' = a/ ω₀ = b/(2m ω₀)
Tan Ф' = ω'/a = √[ 4m² ω₀²/ b² - 1 ] = √[ ω₀²/a² - 1 ]      --- (10)
in terms of initial value of  displacement x = x₀ at t = 0sec and initial velocity v₀ = dx/dt at t = 0sec of the damped oscillations,
Tan Ф' =  ω' x₀ / [ v₀ +  a x₀ ]

x =  A_t  e^{ -bt /(2m) }  Sin [ ω' t  + Ф' ]      -- (11)

A_t  = x₀ Cosec Ф'    from eq (3)
=  √ [ x₀² + (v₀ +  a x₀)² / ω'²  ]